Liverpool Merchants in 19th-Century Niger Delta - Wariboko, Nimi (Social sciences and missions, 2018)
How does religion or worldview affect business practices and ethics? This tradition of inquiry goes back, at least, to Max Weber who, in the Protestant Ethic and the Spirit of Capitalism, explored the impact of theological suppositions on capitalist economic development. But the connection can also go the other way. So the focus of inquiry can become: How does business ethics or practices affect ethics in a given nation or corporation? This paper inquires into how the political and economic conditions created and sustained by nineteenth-century trading community in the Niger Delta influenced religious practices or ethics of Christian missionaries. This approach to mission study is necessary not only because we want to further understand the work of Christian missions and also to tease out the effect of business ethics on religious ethics, but also because Christian missionaries came to the Niger Delta in the nineteenth century behind foreign merchants.